ОПТИМІЗАЦІЯ СКЛАДУ ЖЕЛЮЮЧИХ АГЕНТІВ НА РЕГЕНЕРАЦІЮ МІКРОРОСЛИН КАРТОПЛІ, ОТРИМАНИХ IN VITRO - Шевага, Г. М.; Кирик, М. М.; Гунчак, В. М.; Олійник, Т. М. (Institute of Agrocultural Microbiology and Agro-industrial Manufacture of NAAS of Ukraine, 2016)
Results of studies on the optimization of Murashige and Skoog culture medium withmodified maize starch for the acceleration of potato plants micropropogation are provided. Ithas been established that the method modification increases surveillance parameters, promotesactive in vitro growth and development of potato springs.